Fluoride-ion secondary battery
By using silver and scandium fluoride as electrode materials in fluoride secondary batteries and combining with sulfide electrolytic layer, the problem of traditional fluoride ion batteries not being able to work normally at room temperature and reducing charge and discharge efficiency is solved, and efficient room temperature charging and discharge and cycle stability is achieved.
Patent Information
- Application Number
- JP2021010584
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-01-26
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2041-01-26
AI Technical Summary
Traditional fluoride ion secondary batteries cannot work normally at room temperature, and after three charge and discharge cycles, the charge and discharge efficiency is halved, resulting in serious cycle degradation.
A fluoride ion secondary battery structure containing silver (Ag) and scandium fluoride (CeF3 and PbF2) as the positive and negative electrode materials is adopted, and the thickness and structure of the electrode material are optimized in combination with the sulfide electrolytic layer.
It realizes efficient charging and discharging at room temperature, avoids the increase in overvoltage, delays the degradation of the charging and discharging cycle, and maintains high-efficiency battery performance.
Smart Images

Figure 0007670493000001 
Figure 0007670493000002 
Figure 0007670493000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a fluoride ion secondary battery. [Background technology]
[0002] Fluoride ion secondary batteries using fluoride ions as a carrier have been proposed. Fluoride ion secondary batteries are expected to have battery characteristics superior to those of lithium ion secondary batteries, and various studies have been conducted in recent years.
[0003] For example, a fluoride ion secondary battery has been proposed that includes a positive electrode, a negative electrode containing at least one of a metal containing at least La and a fluoride containing at least La, an ion conductive medium that conducts fluoride ions, and a storage section that hermetically contains the positive electrode, the negative electrode, and the ion conductive medium and has an oxygen concentration of 2 ppm or less (for example, see Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2017-84506 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, conventional fluoride ion secondary batteries such as those described in Patent Document 1 do not operate unless the temperature is as high as 150° C., and the charge / discharge efficiency is halved after three charge / discharge cycles, resulting in significant cycle deterioration. Therefore, there is a need to develop a fluoride ion secondary battery that can achieve high charge / discharge efficiency at room temperature.
[0006] The present invention has been made in view of the above, and has an object to provide a fluoride ion secondary battery that can achieve high charge / discharge efficiency at room temperature. [Means for solving the problem]
[0007] (1) The present invention provides a fluoride ion secondary battery comprising: a positive electrode layer containing Ag; a negative electrode layer containing at least one of CeF3 and PbF2; and a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer and containing LaF3.
[0008] (2) In the fluoride ion secondary battery of (1), the negative electrode material layer may contain CeF3 and may further include a negative electrode current collector layer made of carbon and disposed outside the negative electrode material layer.
[0009] (3) In the fluoride ion secondary battery of (1), the negative electrode material layer may contain PbF2 and may further include a negative electrode current collector layer made of Pb foil, disposed on the outside of the negative electrode material layer.
[0010] (4) In any one of the fluoride ion secondary batteries (1) to (3), a positive electrode current collector layer made of carbon may be further provided on the outside of the positive electrode material layer.
[0011] (5) In any one of the fluoride ion secondary batteries (1) to (4), the positive electrode layer may have a thickness of 10 nm or more and less than 120 nm.
[0012] (6) In the fluoride ion secondary battery of any one of (1) to (5), the positive electrode layer may have a thickness of 10 nm or more and 60 nm or less.
[0013] (7) In any one of the fluoride ion secondary batteries (1) to (6), the positive electrode layer may have a thickness of 10 nm or more and 30 nm or less.
[0014] (8) In any one of the fluoride ion secondary batteries (1) to (7), the negative electrode layer may have a thickness of 10 nm or more and less than 200 nm.
[0015] (9) In any one of the fluoride ion secondary batteries (1) to (8), the negative electrode layer may have a thickness of 10 nm or more and 50 nm or less. Effect of the Invention
[0016] According to the present invention, it is possible to provide a fluoride ion secondary battery that can achieve high charge / discharge efficiency at room temperature. [Brief description of the drawings]
[0017] [Figure 1] 1 is a diagram showing a configuration of a fluoride ion secondary battery according to a first embodiment. [Diagram 2] 2A to 2C are diagrams illustrating an example of a method for manufacturing the fluoride ion secondary battery according to the first embodiment. [Diagram 3] FIG. 2 is a diagram showing charge / discharge curves of the fluoride ion secondary battery according to Example 1. [Figure 4] FIG. 4 is a diagram showing the relationship between the square root of the number of cycles and the capacity of the fluoride ion secondary battery according to Example 1. [Diagram 5] FIG. 4 is a diagram showing the relationship between the square root of the number of cycles and the charge / discharge efficiency of the fluoride ion secondary battery according to Example 1. [Figure 6] FIG. 1 is a diagram showing a configuration of a fluoride ion secondary battery according to Example 2. [Figure 7] FIG. 2 is a diagram showing the configuration of a fluoride ion secondary battery according to Comparative Examples 1 and 2. [Figure 8] FIG. 13 is a diagram showing intermittent charge / discharge curves of the fluoride ion secondary batteries according to Example 2 and Comparative Examples 1 and 2. [Figure 9] FIG. 1 is a diagram showing charge / discharge curves of the fluoride ion secondary batteries according to Comparative Examples 1 to 6. [Figure 10] FIG. 11 is a diagram showing a configuration of a fluoride ion secondary battery according to Example 3. [Figure 11] FIG. 11 is a diagram showing charge / discharge curves of a fluoride ion secondary battery according to Example 3. [Figure 12] FIG. 11 is a diagram showing the relationship between the square root of the number of cycles and the capacity of the fluoride ion secondary battery according to Example 3. [Figure 13] FIG. 11 is a diagram showing the relationship between the square root of the number of cycles and the charge / discharge efficiency of the fluoride ion secondary battery according to Example 3. [Figure 14]FIG. 4 is a diagram showing the relationship between the square root of the number of cycles and the discharge capacity retention rate of the fluoride ion secondary batteries according to Examples 1 and 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings.
[0019] Fig. 1 is a diagram showing the configuration of a fluoride ion secondary battery 1 according to the first embodiment. As shown in Fig. 1, the fluoride ion secondary battery 1 according to the present embodiment includes a positive electrode material layer 11, a negative electrode material layer 13, and a solid electrolyte layer 15 disposed between the positive electrode material layer 11 and the negative electrode material layer 13.
[0020] The positive electrode layer 11 contains Ag. Preferably, the positive electrode layer 11 is made of only Ag. The positive electrode layer 11 converts fluoride ions F - During charging, fluoride ions F - The positive electrode layer 11 made of Ag has a feature of having a small overvoltage at room temperature. The positive electrode layer 11 made of Ag is formed by, for example, sputtering as described later.
[0021] The thickness of the positive electrode layer 11 is preferably 10 nm or more and less than 120 nm. If the thickness of the positive electrode layer 11 is less than 10 nm, it is not preferable because it is not possible to form a film in a particle or island state, or even if a film can be formed, it may cause uneven reaction. Also, if the thickness of the positive electrode layer 11 exceeds 120 nm, it is not preferable because the overvoltage increases and the charge / discharge efficiency decreases. The thickness of the positive electrode layer 11 is more preferably 10 nm or more and 60 nm or less, and even more preferably 10 nm or more and 30 nm or less. FIG. 1 shows an example in which the thickness of the positive electrode layer 11 is 30 nm.
[0022] The negative electrode layer 13 is composed of at least one of CeF3 and PbF2. Preferably, the negative electrode layer 13 is composed of CeF3. The negative electrode layer 13 converts fluoride ions F -During charging, it absorbs fluoride ions F - The negative electrode layer 13 made of at least one of CeF3 and PbF2 has a feature of having a small overvoltage at room temperature. The negative electrode layer 13 containing at least one of CeF3 and PbF2 is formed by sputtering, for example, as described later.
[0023] The thickness of the negative electrode layer 13 is preferably 10 nm or more and less than 200 nm. If the thickness of the negative electrode layer 13 is less than 10 nm, it is not preferable because the film cannot be formed in a particle or island state, or even if the film can be formed, it causes uneven reaction. Also, if the thickness of the negative electrode layer 13 exceeds 200 nm, it is not preferable because the overvoltage increases and the charge / discharge efficiency decreases. The more preferable thickness of the negative electrode layer 13 is 10 nm or more and 100 nm or less, and even more preferably 10 nm or more and 50 nm or less. FIG. 1 shows an example in which the thickness of the negative electrode layer 13 is 50 nm.
[0024] The negative electrode layer 13 may further include a solid electrolyte made of, for example, a fluoride ion-conductive fluoride, a conductive assistant, etc. The negative electrode layer 13 may also include other components such as a binder, etc., as long as the effects of the present embodiment are not impaired.
[0025] The fluoride ion conductive fluoride may be any fluoride having fluoride ion conductivity, for example, CeBaF x and BaLaF y Examples of fluoride ion conductive fluorides include those mentioned above. By including these fluoride ion conductive fluorides, the fluoride ion conductivity is improved.
[0026] The conductive assistant may be any one having electronic conductivity, such as carbon black. Examples of carbon black include furnace black, ketjen black, and acetylene black. By including such a conductive assistant, electronic conductivity is improved.
[0027] The solid electrolyte layer 15 is composed of LaF3. The solid electrolyte layer 15 made of LaF3 has excellent fluoride ion F - It has conductivity. As the solid electrolyte layer 15 made of LaF3, a commercially available LaF3 substrate can be used. The thickness of the solid electrolyte layer 15 is not particularly limited, but is preferably, for example, 0.1 mm to 0.5 mm. FIG. 1 shows an example in which the thickness of the solid electrolyte layer 15 is 0.5 mm.
[0028] Moreover, the fluoride ion secondary battery 1 according to this embodiment preferably includes a positive electrode collector layer 12 disposed on the outside of the positive electrode material layer 11. The positive electrode collector layer 12 may be any material having electronic conductivity, and is not limited thereto. For example, a positive electrode collector layer 12 made of carbon is preferably used. The thickness of the positive electrode collector layer 12 is not particularly limited, and FIG. 1 shows an example in which the thickness of the positive electrode collector layer 12 is 30 nm.
[0029] Moreover, the fluoride ion secondary battery 1 according to this embodiment preferably includes a negative electrode collector layer 14 disposed on the outside of the negative electrode material layer 13. The negative electrode collector layer 14 may be any material having electronic conductivity, and is not limited thereto. For example, when the negative electrode material layer 13 contains CeF3, a negative electrode collector layer 14 made of carbon is preferably used. On the other hand, when the negative electrode material layer contains PbF2, a negative electrode collector layer made of Pb foil is preferably used. The thickness of the negative electrode collector layer 14 is not particularly limited, and FIG. 1 shows an example in which the thickness of the negative electrode collector layer 14 is 30 nm.
[0030] The fluoride ion secondary battery 1 according to this embodiment having the above-mentioned configuration preferably further includes an exterior body such as a coin cell or a laminate cell.
[0031] The shape and size of the fluoride ion secondary battery 1 according to this embodiment are not particularly limited. Fig. 1 shows an example of a cylindrical shape. Also, an example is shown in which the diameters of the positive electrode material layer 11, the positive electrode current collector layer 12, the negative electrode material layer 13, and the negative electrode current collector layer 14 are φ8 mm, and the diameter of the solid electrolyte layer 15 is φ10 mm. By increasing the diameter of the solid electrolyte layer 15 in this way, short-circuiting between the positive electrode and the negative electrode is suppressed.
[0032] Next, a method for producing the fluoride ion secondary battery according to this embodiment will be described in detail with reference to FIG.
[0033] Fig. 2 is a diagram showing an example of a method for manufacturing a fluoride ion secondary battery according to this embodiment. As shown in Fig. 2, first, a LaF3 substrate as a solid electrolyte layer 15 is set in a predetermined jig (not shown) without exposure to the atmosphere (for example, in an environment with a dew point of 80°C or less and an oxygen concentration of 1 ppm or less). This operation can be performed, for example, in a glove box manufactured by UNICO Corporation that is set to the above environment.
[0034] As the LaF3 substrate, a commercially available LaF3 substrate manufactured by, for example, Pier Optics Co., Ltd. can be used. The size of the LaF3 substrate is not particularly limited, but for example, a LaF3 substrate having a diameter of 10 mm and a thickness of 0.5 mm can be used. In addition, it is preferable to use a LaF3 substrate having a mirror-finished surface.
[0035] Next, the LaF3 substrate set on the jig is transported into the chamber of a sputtering device while maintaining the above environment. As the sputtering device, a commercially available sputtering device such as the sputtering device "EB1000" manufactured by Canon Anelva Corporation can be used. The degree of vacuum in the chamber before film formation is, for example, 5×10 -4 Pa or less.
[0036] Next, DC sputtering is performed using the above sputtering device to form a positive electrode layer 11 made of Ag on one surface of the LaF3 substrate as the solid electrolyte layer 15. After the film formation, the process is paused for a predetermined period of time.
[0037] Next, DC sputtering is carried out on the formed positive electrode material layer 11 using the above-mentioned sputtering device, thereby forming a positive electrode current collector layer 12 made of carbon.
[0038] Next, the LaF3 substrate having the positive electrode layer 11 and the positive electrode current collector layer 12 formed in this order on one surface thereof as the solid electrolyte layer 15 is transported from the chamber of the sputtering device into the glove box while maintaining the above environment. After transportation, the LaF3 substrate is removed from the jig, turned over, and set back on the jig with the other surface facing up.
[0039] Next, the LaF3 substrate is turned over and set again on the jig, and transported into the chamber of the sputtering device while maintaining the above environment. After transport, RF sputtering is performed using the sputtering device, so that a negative electrode layer 13 made of CeF3 is formed on the other surface of the LaF3 substrate as the solid electrolyte layer 15. A negative electrode layer made of PbF2 can also be formed by the same procedure.
[0040] Next, the above-mentioned sputtering device is used to perform DC sputtering on the formed negative electrode material layer 13 to form a negative electrode current collector layer 14 made of carbon. A positive electrode current collector layer made of Pb foil can also be formed by the same procedure.
[0041] Next, the LaF3 substrate as the solid electrolyte layer 15 having the negative electrode material layer 13 and the negative electrode current collector layer 14 formed in this order on the other surface is transported from the chamber of the sputtering device into the glove box while maintaining the above environment. After transportation, an exterior body such as a coin cell or a laminate cell is attached and assembled to obtain the fluoride ion secondary battery 1 according to this embodiment.
[0042] The film thickness of each layer can be controlled by verifying the film formation rate in advance and adjusting the sputtering time based on the film formation rate. Specifically, for example, after performing each sputtering film formation under certain conditions with a masking tape such as Kapton tape attached to a part of a quartz plate, the masking tape is peeled off and the step (film thickness) between the part masked with the masking tape and the part not masked with the masking tape is measured with a step gauge. Then, a calibration curve is created from the results of the measurements while changing the conditions of each sputtering film formation to determine the film formation rate. This makes it possible to control the thickness of each film to a desired thickness.
[0043] Next, the cell capacity of the fluoride ion secondary battery 1 according to this embodiment will be described. In one example of the fluoride ion secondary battery 1 according to this embodiment shown in FIG. 1, the capacities of the positive electrode half-cell and the negative electrode half-cell are as follows:
[0044] [Positive half cell] Theoretical capacity: 248mAh / g Density: 10.49g / cm 3 Film thickness: 30 nm Electrode area: 0.5cm 2 Battery capacity: 3.92μAh
[0045] [Negative half cell] Theoretical capacity: 408mAh / g Density: 6.77g / cm 3 Film thickness: 50 nm Electrode area: 0.5cm 2 Battery capacity: 6.9μAh
[0046] In the example of the fluoride ion secondary battery 1 according to the present embodiment, since the theoretical capacity of the positive electrode is smaller as described above, the cell capacity is determined by the theoretical capacity of the positive electrode. That is, the cell capacity of the example of the fluoride ion secondary battery 1 according to the present embodiment shown in FIG. 1 is the capacity of the positive electrode of 3.92 μAh, and the N / P ratio is 3.92 / 6.9=1.76.
[0047] The fluoride ion secondary battery 1 according to this embodiment having the above-mentioned configuration provides the following effects. The fluoride ion secondary battery 1 according to this embodiment is configured to include a positive electrode layer 11 containing Ag, a negative electrode layer 13 containing at least one of CeF3 and PbF2, and a solid electrolyte layer 15 containing LaF3 arranged between the positive electrode layer 11 and the negative electrode layer 13. That is, the fluoride ion secondary battery 1 according to this embodiment is configured by selecting materials that have a small overvoltage even when operated at room temperature through a half-cell charge / discharge test and an intermittent charge / discharge test. Therefore, even when operated at room temperature, it is possible to avoid the occurrence of a large overvoltage, so that charge / discharge cycle deterioration can be suppressed and high charge / discharge efficiency can be obtained.
[0048] The present invention is not limited to the above-described embodiment, and the present invention includes modifications and improvements within the scope that can achieve the object of the present invention. EXAMPLES
[0049] Next, examples of the present invention will be described, but the present invention is not limited to these examples.
[0050] [Example 1] As Example 1, the fluoride ion secondary battery according to the first embodiment shown in Fig. 1 was fabricated according to the above-mentioned manufacturing method. A constant current (CC) charge / discharge test was carried out on the fabricated fluoride ion secondary battery according to Example 1 under the following conditions.
[0051] The CC charge-discharge test was performed under vacuum at room temperature of 25°C (1×10 -4 The test was carried out at a pressure of 1000 V or less (1 Pa or less). In the fluoride ion secondary battery according to Example 1, the cell capacity is determined by the theoretical capacity of 248 mAh / g of the positive electrode made of Ag, which has a smaller theoretical capacity than the negative electrode made of CeF3, so the current load was set to 200 nA, which corresponds to 1 / 20 C of the theoretical capacity of 248 mAh / g of the positive electrode made of Ag. The cell area of Example 1 was about 0.5 cm 2Therefore, this current load is approximately 0.4 μA / cm 2 The cut-off conditions were a cut-off voltage of 1.0 to 4.2 V or a cut-off time of 20 hours. A 10-minute pause was allowed between each charge and discharge switch.
[0052] The charge-discharge test procedure consisted of a rate test for the first 10 cycles. Specifically, the rate was gradually increased to 1 / 20C for cycles 1-3, 1 / 10C for cycles 4-6, 1C for cycles 7-8, and 5C for cycles 9-10. After the rate test, a charge-discharge test was performed for 100 consecutive cycles at a rate of 1C. In the middle of the test, the rate was changed to 1 / 20C to check the charge-discharge capacity. The charge-discharge test results are shown in Figures 3-5.
[0053] FIG. 3 is a diagram showing a charge / discharge curve of the fluoride ion secondary battery according to Example 1. FIG. 4 is a diagram showing the relationship between the square root of the number of cycles and the capacity of the fluoride ion secondary battery according to Example 1. FIG. 5 is a diagram showing the relationship between the square root of the number of cycles and the charge / discharge efficiency of the fluoride ion secondary battery according to Example 1. Here, FIG. 3 shows a charge / discharge curve obtained by the rate test of the first 10 cycles. Also, FIG. 4 and FIG. 5 show, in addition to the rate test, the charge / discharge capacity and the charge / discharge efficiency obtained by the charge / discharge test of 100 cycles after the rate test.
[0054] As shown in Figs. 3 to 5, it was confirmed that the fluoride ion secondary battery according to Example 1 operates as a battery at room temperature. In addition, it was found that the initial charge / discharge efficiency was 90% at room temperature, and the discharge capacity at 5C relative to the discharge capacity at 0.05C was maintained at 80%, and that the battery had excellent rate characteristics. Furthermore, it was found that the charge / discharge efficiency at 1C charge / discharge cycle was 99% at room temperature, and the capacity retention rate after 100 charge / discharge cycles was 50%. From the above results, it was confirmed that the fluoride ion secondary battery according to Example 1 can achieve high charge / discharge efficiency at room temperature.
[0055] [Example 2] FIG. 6 is a diagram showing the configuration of a fluoride ion secondary battery 1a according to Example 2. As Example 2, the fluoride ion secondary battery 1a shown in FIG. 6 was produced according to the above-mentioned production method. In the fluoride ion secondary battery 1a according to Example 2, the negative electrode material layer 13 made of CeF3 with a thickness of 50 nm in the fluoride ion secondary battery according to Example 1 is changed to a negative electrode material layer 13a made of PbF2 with a thickness of 200 nm, and the negative electrode current collector layer 14 made of carbon with a thickness of 30 nm is changed to a negative electrode current collector layer 14a made of Pb foil with a thickness of 0.2 mm, and it can also be said to be an Ag positive electrode half cell. An intermittent charge and discharge test was carried out under the following conditions for the produced fluoride ion secondary battery according to Example 2.
[0056] The intermittent charge / discharge test was performed under vacuum at room temperature of 25°C (1×10 -5 The intermittent charge-discharge test was carried out at a constant current (Vp) of 100 mA (Pa). Specifically, an intermittent charge-discharge test was carried out by repeatedly performing a 1-hour CC charge and a 5-hour pause, and then repeatedly performing a 1-hour CC discharge and a 5-hour pause. The current load was 400 nA, which corresponds to 1 / 10 C of the positive electrode design capacity, and the voltage was in the range of 0 to 1.7 V. The results of the intermittent charge-discharge test are shown in FIG. 8.
[0057] [Comparative Examples 1 to 6] FIG. 7 is a diagram showing the configuration of the fluoride ion secondary battery 2 according to Comparative Examples 1 to 6. As Comparative Examples 1 to 6, the fluoride ion secondary battery 2 shown in FIG. 7 was produced by the same procedure as the above-mentioned manufacturing method. In the fluoride ion secondary battery 2 according to Comparative Examples 1 to 6, the positive electrode material layer 11 made of Ag with a thickness of 30 nm in the fluoride ion secondary battery 1a according to Example 2 is changed to a positive electrode material layer 21 made of Cu with a thickness of 3 nm, and the thickness of the positive electrode collector layer 12 and the thickness of the negative electrode material layer 13a made of PbF2 are changed to the thickness of the positive electrode collector layer 22 and the thickness of the negative electrode material layer 23 made of PbF2, and it can be said that it is a Cu positive electrode half cell. For the fluoride ion secondary battery shown in FIG. 7, an intermittent charge and discharge test was carried out under the conditions described below. In addition, for the fluoride ion secondary battery shown in FIG. 7, a CC charge and discharge test was carried out under the same conditions as those of Example 1 described above. More specifically, the CC charge-discharge test was performed at room temperature of 25°C in Comparative Example 1, 140°C in Comparative Example 2, 60°C in Comparative Example 3, 80°C in Comparative Example 4, 100°C in Comparative Example 5, and 120°C in Comparative Example 6.
[0058] In the comparative example 1, the intermittent charge-discharge test was performed under vacuum at room temperature of 25°C (1×10 -5 In Comparative Example 2, the temperature was 140° C. under vacuum (1×10 -5 The intermittent charge-discharge test was carried out at a constant current (Vp) of 100 mA (Pa) for each of the comparative examples 1 and 2. Specifically, in both comparative examples 1 and 2, an intermittent charge-discharge test was carried out by repeatedly carrying out a CC charge for 1 hour and a rest for 3 hours, and a CC discharge for 0.5 hours and a rest for 3 hours. The current load was 123 nA, which corresponds to 1 / 10 C of the positive electrode design capacity, and the voltage was in the range of 0.1 to 1.3 V. The results of the intermittent charge-discharge test are shown in FIG. 8.
[0059] Fig. 8 is a diagram showing intermittent charge / discharge curves of the fluoride ion secondary batteries 1a and 2 according to Example 2 and Comparative Examples 1 and 2. In Fig. 8, the height of each peak seen intermittently at the start of charging, i.e., the difference between the OCV and the CCV, represents the magnitude of the overvoltage. In both Example 2 and Comparative Examples 1 and 2, the peaks switch to the negative side midway through, which means that the set charging pressure is reached and the battery switches to discharging. From the results in Fig. 8, it is found that Comparative Examples 1 and 2 reached the set charging pressure earlier than Example 2.
[0060] In addition, as shown in Fig. 8, the Cu positive electrode half-cell of Comparative Example 1, which was subjected to an intermittent charge-discharge test at room temperature, had a very large overvoltage compared to the Ag positive electrode half-cell of Example 2, and the overvoltage further increased as charging proceeded. This was presumed to be due to the ionic conductivity of CuF2 generated in the positive electrode layer made of Cu.
[0061] On the other hand, the overvoltage of the Cu positive electrode half-cell of Comparative Example 2, which underwent an intermittent charge-discharge test at 140°C, was equivalent to that of the Ag positive electrode half-cell of Example 2, which underwent an intermittent charge-discharge test at room temperature, and it was found that charging and discharging close to the theoretical capacity of the positive electrode layer made of Cu was possible. From this result, it was confirmed that it is important to reduce the resistance of the DC component (electron, ion conduction, charge transfer, etc.), which causes overvoltage, for operation at room temperature.
[0062] Fig. 9 is a diagram showing charge / discharge curves of the fluoride ion secondary battery 2 according to Comparative Examples 1 to 6. Fig. 9 shows charge / discharge curves obtained by carrying out a CC charge / discharge test at room temperature of 25°C in Comparative Example 1, 140°C in Comparative Example 2, 60°C in Comparative Example 3, 80°C in Comparative Example 4, 100°C in Comparative Example 5, and 120°C in Comparative Example 6, and it was found that the charge / discharge capacity decreased as the temperature decreased. From this result, it was also confirmed that it is difficult to charge / discharge at room temperature with a positive electrode layer made of Cu.
[0063] [Example 3] Fig. 10 is a diagram showing the configuration of a fluoride ion secondary battery 1b according to Example 3. As Example 3, the fluoride ion secondary battery 1b shown in Fig. 10 was produced according to the above-mentioned production method. In the fluoride ion secondary battery 1b according to Example 3, the thickness of the positive electrode material layer 11 made of Ag in the fluoride ion secondary battery 1 according to Example 1 is changed from 30 nm to 120 nm, and the thickness of the negative electrode material layer 13 made of CeF3 is changed from 50 nm to 200 nm.
[0064] A CC charge-discharge test was carried out on the fabricated fluoride ion secondary battery 1b according to Example 3 under the same conditions as those of Example 1. That is, a rate test was first carried out in which the rate was gradually increased to a faster rate, and then a charge-discharge test was carried out continuously for 100 cycles at a rate of 1C. However, in the rate test of Example 3, the rate was 1 / 20C for 1-3 cycles, 1 / 10C for 4-5 cycles, 1C for 6-7 cycles, and 2C for 8-9 cycles. The charge-discharge test results are shown in Figs. 11 to 15.
[0065] Fig. 11 is a diagram showing charge / discharge curves of the fluoride ion secondary battery 1b according to Example 3. Fig. 12 is a diagram showing the relationship between the square root of the number of cycles and the capacity of the fluoride ion secondary battery 1b according to Example 3. Fig. 13 is a diagram showing the relationship between the square root of the number of cycles and the charge / discharge efficiency of the fluoride ion secondary battery 1b according to Example 3. Fig. 14 is a diagram showing the relationship between the square root of the number of cycles and the discharge capacity retention rate of the fluoride ion secondary battery 1b according to Examples 1 and 3.
[0066] Comparing the charge / discharge curve of the fluoride ion secondary battery 1b according to Example 3 shown in Fig. 11 with the charge / discharge curve of the fluoride ion secondary battery 1 according to Example 1 shown in Fig. 3 above, it was found that the charge / discharge capacity decreased more significantly and the overvoltage increased more significantly when the rate was increased to 1C and 2C in Example 3. From this result, it was confirmed that the preferable upper limit value of the thickness of the positive electrode material layer made of Ag is less than 120 nm, and the preferable upper limit value of the thickness of the negative electrode material layer made of CeF3 is less than 200 nm.
[0067] Comparing the relationship between the square root of the number of cycles and the capacity and charge / discharge efficiency of the fluoride ion secondary battery 1b according to Example 3 shown in FIG. 12-FIG. 13 and the relationship between the square root of the number of cycles and the capacity and charge / discharge efficiency of the fluoride ion secondary battery 1 according to Example 1 shown in FIG. 4 and FIG. 5 described above, it was found that Example 3 had a larger decrease in charge / discharge capacity and charge / discharge efficiency in the initial rate test. In addition, it was found that the charge / discharge efficiency during 100 cycles of charge / discharge at a rate of 1C was about 98% in Example 3, which was slightly worse than that in Example 1. It was also found that the cycle durability deterioration in Example 3 was worse. This was presumed to be due to film peeling of each layer due to volume change. From these results, it was confirmed that the preferable upper limit value of the film thickness of the positive electrode material layer made of Ag is less than 120 nm, and the preferable upper limit value of the film thickness of the negative electrode material layer made of CeF3 is less than 200 nm.
[0068] From the relationship between the square root of the number of cycles and the discharge capacity retention rate of the fluoride ion secondary batteries 1 and 1b according to Examples 1 and 3 shown in Fig. 14, it was found that the deterioration due to the 1C cycle durability test was greater in Example 3 than in Example 1. However, it was found that the discharge capacity retention rate returned to normal in Example 3 during the capacity confirmation at 1 / 20C rate. From this result, it was also confirmed that the preferable upper limit value of the thickness of the positive electrode material layer made of Ag is less than 120 nm, and the preferable upper limit value of the thickness of the negative electrode material layer made of CeF3 is less than 200 nm. [Explanation of symbols]
[0069] 1,1a,1b Fluoride-ion secondary battery 11 Cathode material layer 12 Positive electrode current collector layer 13,13a Negative electrode material layer 14, 14a Negative electrode current collector layer 15 Solid electrolyte layer
Claims
1. A positive electrode layer containing Ag; CeF 3 and PbF 2 A negative electrode material layer including at least one of LaF is disposed between the positive electrode layer and the negative electrode layer. 3 and a solid electrolyte layer comprising: The film thickness of the positive electrode layer is 10 nm or more and less than 120 nm.
2. 2. The fluoride ion secondary battery according to claim 1, wherein the positive electrode layer has a thickness of 10 nm or more and 30 nm or less.
3. 3. The fluoride ion secondary battery according to claim 1, wherein the negative electrode layer has a thickness of 10 nm or more and less than 200 nm.
4. 4. The fluoride ion secondary battery according to claim 3, wherein the negative electrode layer has a thickness of 10 nm or more and 50 nm or less.
5. A positive electrode layer containing Ag; CeF 3 and PbF 2 A negative electrode material layer including at least one of LaF is disposed between the positive electrode layer and the negative electrode layer. 3 and a solid electrolyte layer comprising: The film thickness of the negative electrode layer is 10 nm or more and less than 200 nm.
6. 6. The fluoride ion secondary battery according to claim 5, wherein the negative electrode layer has a thickness of 10 nm or more and 50 nm or less.
Citation Information
Patent Citations
Solid-state secondary power supply
JP2008537312A
Solid-state chemical current source and method for enhancing discharge output
JP2009523298A
Fluoride ion secondary battery
JP2017084506A
Fluoride ion battery
JP2019192581A